(untitled) (The Journal of Theoretical Accounting Research, 2025)
This study advanced the understanding of managerial accounting performance indicators by analyzing the joint impact of climatic variations and price indices on Spanish hotels. This analysis used a nonlinear regression framework with tensor product smooth functions to capture dynamic interactions between temperature, rainfall, and pricing decisions based on accounting frameworks. The focus of the study was to determine how these interactions affect accounting-based performance measurement across different hotel categories, from one-star to five-star. This study reveals significant nonlinear effects of climatic variables on accounting performance and observes that managerial accounting performance indicators are contingent on pricing strategies and hotel categories. Luxury hotels exhibit higher variability in fluctuations, whereas budget hotels are less affected due to their inelastic demand, influencing accounting performance metrics. Therefore, this study extended the cost management theory by integrating the accounting performance of the hospitality sector on account of the fusion of climate variability and prices across different hotel categories. This study contributes to accounting frameworks and cost management theory by linking climate and pricing effects to decision-making in accounting. The findings provide implications for accounting thought and performance measurement in sustainability contexts.